REVIEWS - Watson, Wilfred G. E. 20./21. Jh. (Journal of Semitic studies, 2003)
West Semitic Vocabulary in the Akkadian Texts from Emar (Harvard Semitic Studies 49) Eugen J. Pentiuc . Eisenbrauns, Winona Lake 2001. Pp. xvii + 278. Price: $36.95 hardback. ISBN: 1-57506-910-5.